Stress and the neuroendocrinology of anxiety disorders - Pêgo, José M. (2010)
Stress is a risk factor for depressive and anxiety disorders. Changes in lifestyle patterns that are associated with increased stress therefore place a greater burden on mental health. Stress challenges the organism's homeostatic mechanisms, triggering a cascade of events that should, normally, maintain or allow a return to equilibrium. Stressful events are perceived by sensory systems in the brain, facilitating evaluation and comparison of the existing and previous stimuli as well as the activation of hormones responsible for energy mobilization. The limbic system coordinates the release of corticosteroids, the primary stress hormones, by modulating activation of the hypothalamic paraventricular nucleus (PVN). The amygdala, a limbic structure related to emotional behavior, has a putative role in the evaluation of emotional events and formation of fearful memories; it is also a target of the neurochemical and hormonal mediators of stress. Clinical and experimental data have correlated changes in the structure/function of the amygdala with emotional disorders such as anxiety. In this chapter we review the neuroendocrinology of the stress response, focusing on the role of the limbic system in its establishment and supplementing that information with new experimental data that demonstrates the relationship between stress and anxiety disorders; we also discuss the structural changes that occur in the amygdala after stress.